Development and testing of zinc sulfate and zinc oxide nanoparticle-coated urea fertilizer to improve N and Zn use efficiency - Beig, Bilal; Niazi, Muhammad Bilal Khan; Jahan, Zaib; Haider, Ghulam; Zia, Munir; Shah, Ghulam Abbas; Iqbal, Zahid; Hayat, Asim (Frontiers in Plant Science, 2023)
Nitrogen (N) losses from conventional fertilizers in agricultural systems are very high, which can lead to serious environmental pollution with economic loss. In this study, innovative slow-release fertilizers were prepared using zinc (Zn) [nanoparticles (NPs) or in bulk], using molasses as an environmentally friendly coating. Several treatments were prepared using Zn in different concentrations (i.e., 0.25%, 0.5%, and 4% elemental Zn). The zinc oxide nanoparticles (ZnO-NPs) were prepared from zinc sulfate heptahydrate (ZnSO4·7H2O), and were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Furthermore, the Zn-loaded urea samples were tested for urea N release rate, leaching of water from soil, and crushing strength to assess the impact of coating on the final finished product. Pot experiments were conducted simultaneously to check the agronomic effects of Zn-coated slow-release urea on the growth and development of wheat (Triticum aestivum L.). The laboratory and pot results confirmed that the ZnO-NP treatments boost wheat growth and yield as a result of reduced N and Zn release. UZnNPs2 (urea coated with 0.5% ZnO-NPs and 5% molasses) demonstrated the best results among all the treatments in terms of slow nutrient release, N and Zn uptake, and grain yield. The UZnNPs2 treatment increased plant yield by 34% (i.e., 4,515 vs. 3,345 kg ha–1) relative to the uncoated prill-treated crop because of the slower release of Zn and N.